EL MUSEO NACIONAL DE COLOMBIA Y LAS REPRESENTACIONES DE LO NACIONAL: REFLEXIONES SOBRE LA PAZ Y LA GLOBALIZACIÓN - Vanegas Muñoz, Laura Ximena (2018)
This article aims to study how the Museo Nacional in Colombia, reflects diverse transformations in the ways of representing the national, which are coherent with the political constitutions of 1886 and 1991 of the country. The National Museum as a space of exhibition and narrative construction, seeks to influence Colombian identity and national memory. The Museum it’s going through various situations of change that allow us to address paradigms within the ways of questioning, the concept of national Especially at a time when the country is undergoing a process of peace and in a world in which borders are increasingly more blurred by the processes of globalization.